1967
DOI: 10.1099/00221287-47-3-389
|View full text |Cite
|
Sign up to set email alerts
|

The uptake and fate of Isoniazid in Mycobacterium tuberculosis var. bovis BCG

Abstract: S U M M A R YThe incorporation of 14C INH into sensitive and resistant bacteria has been investigated. Only organisms susceptible to INH took up the drug. Uptake was irreversible and became saturated at higher INH concentrations. Uptake was heat-labile, KCN-sensitive, partially inhibited by dinitrophenol and stimulated by SH group reagents. The activation energy of binding was of the same order as the activation energy of an enzyme catalysed reaction. Uptake at 37" was rapidly inhibited although at 4" it was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

1968
1968
1998
1998

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…It has been shown that 4 × 10 −4 M dinitrophenol induces a 50% inhibition of labelling by [ 14 C]INH in Mycobacterium bovis BCG (Wimpenny, 1967), suggesting that uptake could result from active secondary transport. However, this experiment again used a long uptake time (40 h).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that 4 × 10 −4 M dinitrophenol induces a 50% inhibition of labelling by [ 14 C]INH in Mycobacterium bovis BCG (Wimpenny, 1967), suggesting that uptake could result from active secondary transport. However, this experiment again used a long uptake time (40 h).…”
Section: Resultsmentioning
confidence: 99%
“…1). In fact, the level of cell-bound drug seemed to fall off gradually, which might reflect INH metabolism by the tubercle bacillus (11,13). In early preliminary work, we observed that NH protects tubercle bacilli from INH growth inhibition and is itself not inhibitory to the organism at a concentration of 10 Ag/ml.…”
Section: Resultsmentioning
confidence: 78%
“…It is also possible that, after incubation of "4C-INH-containing cells for several hours in a medium devoid of INH, a significant proportion of the cell-bound 14C activity is no longer INH, but rather some product of its metabolism (11,13). If this were true, it would not necessarily weaken the idea that a critical level of active INH is maintained under conditions where further INH uptake is blocked by NH.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the reported differences involve growth rate, virulence, and degrees of drug resistance (21). Most strains which develop INH-resistance also undergo enzymatic changes, such as losses in catalase and peroxidase activity (7,14), and lose the capacity to accumulate the drug intracellularly (19). The experiments reported here were carried out to investigate the possibility that these changes are associated with alterations in antigenicity of these organisms, and significant antigenic differences were found between an INH-resistant mutant and its parent strain.…”
mentioning
confidence: 99%